دور لغة الجسد في تعليم اللغة العربية لغير الناطقين بها من خلال درس المفردات نموذجا - Fahmi Ridha (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
This research aims to reveal and know the importance of the role of body language in teaching Arabic to non-native speakers, especially in teaching vocabulary. This research depends on the qualitative and descriptive approach, where data is collected by looking at some books that contain topics of body language and vocabulary education as being from the primary sources, as well as all references related to this research from scientific research, refereed journals, articles and periodicals, and others as secondary sources. And the researcher may resort to some considered addresses documented in the international network of additional information. The result of this study was a The role of body language in teaching vocabulary is very important, through which the student can understand the meanings of the targeted vocabulary easily and these meanings are firmly established in his mind. The importance of body language in actual teaching using the non-linguistic method is shown in explaining the meanings of the targeted vocabulary in one of the following methods: meaning representation, role representation, position and context, reference and presentation, and direct experience. In applying this method, the following basic principles should be observed : An appropriate method in a statement meaningful significant words, not to explain more than one word at the same time, one word target recording on the blackboard by typing clear and the size of a large, repeat target words identical to the statement of movements, signs and gestures, and others, attention attracted students to focus on the statement and try to explain the desired meaning, not to increase the non-targeted alien word when making the statement, using the method of explanation as it suits the type of target words, giving the learner the opportunity to repeat the targeted words in accordance with the statement of movements, signs, gestures, etc.